Հայկական հարցի 1919−1920 թթ. պատմության լուսաբանումը Հայաստանի պատմագրության մեջ (1991−2019 թթ.) - Լիլիթ Հովհաննիսյան (ՀՀ ԳԱԱ հրատ.)
В 1991–2019 гг. в историографии Армении была проделана ценная работа по переосмыслению содержания и результатов дипломатических переговоров на Парижской международной мирной конференции и в Лиге наций, а также проходивших в 1919–1920 гг. в армянских общественно-политических кругах дискуссий о независимости, границах и мандате Западной Армении. В частности, всесторонне исследована и оценена политика Великобритании и США в Армянском вопросе. Выявлены практические возможности и перспективы осуществления мандата на Армению. Также проанализированы причины отсутствия единой всеармянской позиции по решению Армянского вопроса. Политическое значение Севрского договора и Арбитражного решения Вудро Вильсона 1920 г. переоценены с точки зрения армянских национальных интересов. A valuable work has been done in the historiography of Armenia in 1991–2019 on the recomprehending of the content and results of diplomatic negotiations at the 1919–1920 Paris International Peace Conference and the League of Nations, as well as discussions held in the Armenian socio-political circles on the independence, boundaries and mandate of Western Armenia. In particular, the policy of Great Britain and the USA in the Armenian question is studied and assessed comprehensively. The practical possibilities and prospects of realization of the mandate for Armenia are revealed. Also the reasons of absence of the pan-Armenian position on the solution of the Armenian question are analyzed. The political importance of the 1920 Treaty of Sèvres and Woodrow Wilsons Arbitral Award is re-evaluated from the point of view of the Armenian national interests.
Keywords: History; D History; Հայկական հարց